A readership survey of Western Pacific Surveillance and Response Journal - McPherson, Michelle; Mangali, Elizabeth; Fielding, James; Gregory, Joy; Li, Ailan (Western Pacific Surveillance and Response, 2015)
A short editorial on the readership survey on WPSAR